A Liminal Press: Situating News App Designers Within a Field of Networked News Production - Ananny, Mike; Crawford, Kate (Digital Journalism, 2014)
In this project we use interview data from the US and Europe to map field dynamics within an emerging techno-journalistic space of news app design. We describe this space in terms of institutional theory and field-level studies of news production and report on a series of interviews we conducted with senior news app designers and lead programmers. Part of a larger empirical study on mobile news app design, we focus here on analyzing how designers understand their work in relation to journalism as a profession and process, and how they see themselves as like or unlike others in their field. We conclude with reflections on how these designers are helping to constitute the organizational field of news app design by creating and sustaining boundary infrastructures that constitute an emerging “liminal press”.